Pertanggungjawaban Hukum Rumah Sakit atas Kebocoran Data Rekam Medis Elektronik Pasien - Dame, Andrew Reforto Ondo; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The digital transformation of healthcare services has accelerated the adoption of Electronic Medical Records (EMRs) in hospitals, while simultaneously increasing the risk of patient data breaches. This study aims to analyze the legal framework governing the protection of electronic medical records, examine hospitals' legal liability for data breaches, and evaluate the effectiveness of existing regulations in safeguarding patients' rights. This normative juridical research employs statutory and conceptual approaches, referring to Law Number 17 of 2023 on Health, Law Number 27 of 2022 on Personal Data Protection, the Electronic Information and Transactions Law and its amendments, and Minister of Health Regulation Number 24 of 2022 on Medical Records. The findings indicate that hospitals, as data controllers, may incur civil, administrative, and criminal liability for data breaches. However, legal protection remains constrained by weak enforcement, limited oversight, and inadequate mechanisms for victim recovery.